(untitled) (Kronika Bydgoska, 2013)
Private and family-property archives kept by the State Archive in Bydgoszcz are only a small part of the stocks. They refer to the area of Pomerania and Wielkopolska. Usually, they are a valuable source material, especially when family members had held high offices or participated actively in the political, social and economic life of the region and Poland. Most of the private archives are significantly broken up and preserved in a residual state. They were lost or damaged during World War Two. The State Archive in Bydgoszcz includes archives of the families: von Alvensleben from Ostromecko, von Bethmann-Hollweg from Runowo Krajeńskie, Bniński from Samostrzel, Gordon from Bzowo, Górski from Kamienica, Tuchola Poviat, Komierowski from Komierowo, Poniński from Kościelec, Potulicki from the Więcbork estate, Sikorski from Wielkie Chełmy, and archives of the properties: Ludwiniec and Jankowo, Brzeście, Głuszyn, Kończyce, Kosowo and Chrostkowo, Kusowo, Łąkocin and Sukowy, Mierzyn, Orle, Pińsko, Polichno, Topola, Retkowo and Królikowo, Tuczno, and Witosław.